Different Approaches to Address Bullying in KiVa Schools: Adherence to Guidelines, Strategies Implemented, and Outcomes Obtained - Johander Eerika; Turunen Tiina; Garandeau Claire; Salmivalli Christina (Springer, 2022)
We examined the extent to which school personnel implementing the KiVa® antibullying program in Finland during 2009–2015 systematically employed the program-recommended approaches (confronting or non-confronting), used one or the other depending on the bullying case (case-specific approach), or used their own adaptation when talking to perpetrators of bullying, and whether they organized follow-up meetings after such discussions. In addition to investigating adherence to program guidelines, we tested how effective these different approaches were in stopping bullying. Finally, we tested the contribution of follow-up meetings and the number of years KiVa had been implemented in a school to the effectiveness of the interventions, using reports from both school personnel and victimized students. The data were collected annually across 6 years via online questionnaires and included responses from 1221 primary and secondary schools. The school personnel were more likely to use the confronting approach than the non-confronting approach. Over time, rather than sticking to the two program-recommended approaches, they made adaptations (e.g., combining the two; using their own approach). Two-level regression analyses indicated that the discussions were equally effective, according to both personnel and victimized students, when the confronting, non-confronting, or a case-specific approach had been used. The discussions were less effective when the personnel used their own adaptation or could not specify the method used. Perceived effectiveness was higher in primary school and when follow-up meetings were organized systematically after each intervention, but unrelated to the number of years KiVa had been implemented.
Over the past decades, growing awareness of the negative outcomes of school bullying (Reijntjes et al. <a title="Reijntjes, A., Kamphuis, J. H., Prinzie, P., & Telch, M. J. (2010). Peer victimization and internalizing problems in children: A meta-analysis of longitudinal studies. Child Abuse & Neglect, 34, 244–252. https://doi.org/10.1016/j.chiabu.2009.07.009 ." href="https://link.springer.com/article/10.1007/s11121-020-01178-4#ref-CR29">2010) has in many countries led to normative regulation, such as schools being required to have a policy, or an action plan against bullying (Salmivalli <a title="Salmivalli, C. (2018). International perspectives on bullying prevention. In Handbook of Child and Adolescent Aggression. New York: The Guilford Press." href="https://link.springer.com/article/10.1007/s11121-020-01178-4#ref-CR35">2018). School personnel are thus faced with a demand to do something to address bullying. At the same time, numerous antibullying programs have been developed and evaluated in different parts of the world (Gaffney et al. <a title="Gaffney, H., Ttofi, M. M., & Farrington, D. P. (2019). Evaluating the effectiveness of school-bullying prevention programs: An updated meta-analytical review. Aggression and Violent Behavior, 45, 111–133. https://doi.org/10.1016/j.avb.2018.07.001 ." href="https://link.springer.com/article/10.1007/s11121-020-01178-4#ref-CR11">2019). Such programs often combine preventive actions (such as student lessons or improved supervision) with targeted interventions (i.e., procedures for intervening in actual bullying cases, such as discussions with the students involved). Evaluation studies have, however, mainly estimated the effects of whole programs (without distinguishing prevention from intervention components), and the few studies that have compared the effectiveness of different approaches in targeted interventions only assessed short-term effectiveness on the basis of a single student informant (Garandeau et al. <a title="Garandeau, C. F., Poskiparta, E., & Salmivalli, C. (2014). Tackling acute cases of school bullying in the KiVa anti-bullying program: A comparison of two approaches. Journal of Abnormal Child Psychology, 42, 981–991. https://doi.org/10.1007/s10802-014-9861-1 ." href="https://link.springer.com/article/10.1007/s11121-020-01178-4#ref-CR12">2014, <a title="Garandeau, C. F., Vartio, A., Poskiparta, E., & Salmivalli, C. (2016). School bullies’ intention to change behavior following teacher interventions: Effects of empathy arousal, condemning of bullying, and blaming of the perpetrator. Prevention Science, 17, 1034–1043. https://doi.org/10.1007/s11121-016-0712-x ." href="https://link.springer.com/article/10.1007/s11121-020-01178-4#ref-CR13">2016). Consequently, we know little about the relative effectiveness of different approaches used when a case of bullying has already occurred, and even less about how school personnel implement guidelines provided to address such cases. The present study investigates the extent to which school personnel implementing the KiVa® antibullying program (Kärnä et al. <a title="Kärnä, A., Voeten, M., Little, T. D., Poskiparta, E., Alanen, E., & Salmivalli, C. (2011a). Going to scale: A nonrandomized nationwide trial of the KiVa antibullying program for grades 1–9. Journal of Consulting and Clinical Psychology, 79, 796–805. https://doi.org/10.1037/a0029174 ." href="https://link.springer.com/article/10.1007/s11121-020-01178-4#ref-CR16">2011a) in Finland employ the program-recommended approaches (confronting vs. non-confronting) when discussing with bullying perpetrators, how this changes over a period of 6 years, and how effective the chosen approaches (whether program-recommended or something else) are perceived to be by the school personnel and by the students who have been victimized.